The Role of E-Business Adoption Towards Improving Msme Performance in Parepare City - Anis Anshari Masud; Nurfadhilah Nurfadhilah; Bakhtiar Tijjang; Rustan Ali (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2022)
This study aims to examine and analyze the effect of integrated information systems, technological innovation, and e-business adoption on improving the performance of MSMEs in the manufacturing sector in Parepare City. The data collection method used a questionnaire that was distributed to 71 business actors using the purposive sampling technique. Members of the population as many as 103 samples consist of business owners and the marketing services. The data were analyzed using SEM from the AMOS version 23 application. The results showed that the integrated information system and technological innovation had a positive and significant impact on improving the performance of MSMEs in Parepare City through the adoption of e-business. Use of e-business as an intervening variable has a positive and significant effect on the performance of MSMEs. The implications of this research are expected to be able to contribute to the progress of research in the scope of management and have an impact on MSME actors, especially MSMEs in Parepare City, both trading and manufacturing, by increasing the ability to implement e-business in business processes that can encourage MSMEs to adapt to information systems that integration and innovation of new technologies. This study uses a theoretical model of Technology, Organization, Environment (TOE), the theory in this study provides support and is proven regarding the factors that can affect the use of e-business in terms of technology, organization, and environment.This study aims to examine and analyze the effect of integrated information systems, technological innovation, and e-business adoption on improving the performance of MSMEs in the manufacturing sector in Parepare City. The data collection method used a questionnaire that was distributed to 71 business actors using the purposive sampling technique. Members of the population as many as 103 samples consist of business owners and the marketing services. The data were analyzed using SEM from the AMOS version 23 application. The results showed that the integrated information system and technological innovation had a positive and significant impact on improving the performance of MSMEs in Parepare City through the adoption of e-business. Use of e-business as an intervening variable has a positive and significant effect on the performance of MSMEs. The implications of this research are expected to be able to contribute to the progress of research in the scope of management and have an impact on MSME actors, especially MSMEs in Parepare City, both trading and manufacturing, by increasing the ability to implement e-business in business processes that can encourage MSMEs to adapt to information systems that integration and innovation of new technologies. This study uses a theoretical model of Technology, Organization, Environment (TOE), the theory in this study provides support and is proven regarding the factors that can affect the use of e-business in terms of technology, organization, and environment.